2005
DOI: 10.1038/sj.bjc.6602854
|View full text |Cite
|
Sign up to set email alerts
|

RASSF2, a potential tumour suppressor, is silenced by CpG island hypermethylation in gastric cancer

Abstract: RASSF2, a member of the RASSF1 family, has recently been identified as a potential tumour suppressor. We examined methylation status in multiple regions which included the CpG island and spanned the transcription start site of RASSF2 in 10 gastric cancer cell lines, as well as 78 primary gastric cancers and corresponding non-neoplastic gastric epithelia. Hypermethylation of RASSF2 in at least one of the regions examined was detected in seven (70%) of the 10 cell lines; two (20%) exhibited hypermethylation in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 25 publications
4
49
0
Order By: Relevance
“…FUS1 was originally identified as a PAP that potentiates and inhibits the mitogenic effect of PDGF-A and PDGF-B, respectively (Fischer and Schubert, 1996) suggesting the protein may indeed play A high-stringency motif scan (scansite.mit.edu) identifies a predicted PKC and PKA kinase site (Ser50) and an ERK binding motif. Myristoylation of FUS1 has also been described (Endoh et al, 2005). ERK, extracellular signal-regulated kinase; PKA, protein kinase A; PKC, protein kinase C.…”
Section: Fus1/tusc2mentioning
confidence: 98%
See 1 more Smart Citation
“…FUS1 was originally identified as a PAP that potentiates and inhibits the mitogenic effect of PDGF-A and PDGF-B, respectively (Fischer and Schubert, 1996) suggesting the protein may indeed play A high-stringency motif scan (scansite.mit.edu) identifies a predicted PKC and PKA kinase site (Ser50) and an ERK binding motif. Myristoylation of FUS1 has also been described (Endoh et al, 2005). ERK, extracellular signal-regulated kinase; PKA, protein kinase A; PKC, protein kinase C.…”
Section: Fus1/tusc2mentioning
confidence: 98%
“…The feasibility of using RASSF2A methylation as a biomarker for CRCs, perhaps in combination with other genes, is an area of current research in our laboratory. RASSF2A methylation has also been found in gastric cancer at frequencies ranging from 29 to 79% and in 51% of NPC primary tumours (Endoh et al, 2005;Zhang et al, 2007). In NPC tumours RASSF2A methylation correlates with increased metastatic potential (Zhang et al, 2007).…”
Section: Rassf1mentioning
confidence: 99%
“…On the other hand, Endoh et al (25) carried out the first detailed investigation and determined that frequent silencing of RASSF2 was associated with promoter hypermethylation in gastric cancer. Their study revealed that methylation frequencies of RASSF2 varied in the regions upstream and downstream of the transcription start site.…”
Section: Discussionmentioning
confidence: 99%
“…13,17,18 Although the exact mechanisms about how RASSF2 functions in human cancers were largely unknown, inactivation of RASSF2 in kidney cells showed an advanced growth during transformation, 18 and in vitro expression of RASSF2 could induce apoptosis and cell cycle arrest in lung cancer cells. 9 In our study, we further confirmed the ability of RASSF2 to induce cell cycle arrest and inhibit colony formation in NPC cells.…”
Section: Discussionmentioning
confidence: 99%